Agonist stimulus trafficking by human prostanoid CRTH2 (DP2) receptors. - McArthur Wilson, Richard John (2007)
Agonists of hormone receptors possess affinity (the ability to bind) & efficacy (the ability to stimulate effect). In this thesis, alternative expressions of efficacy by recombinant prostanoid Chemoattractant Receptor Homologous molecule of TH2 cell (hCRTH2) receptors have been studied using a variety of assays and pharmacological techniques. When expressed in CHO cells, either with or without co-expression of chimeric G alpha 16z49 G-proteins, CRTH2 receptor-mediated calcium mobilisation pharmacology was found to be as published. Coupling of receptor activation to calcium elevation involved G beta gamma i/o mediated PLC beta -dependent mobilisation of both intra- & extra- calcium. In chimera-expressing cells, an additional coupling mechanism was observed which was presumably G alpha 16z49-mediated. The relative expression of receptor and G-protein molecules in both cell types was investigated but because of deficiencies in the methods employed the relative expression is essentially unknown. Because G alpha 16z49 & G beta gamma i/o represent different classes of PLC beta -activating G-proteins, simultaneous activation of them may have produced a synergistic response in chimera-expressing cells which may have affected the observed receptor pharmacology. When the G alpha 16z49 component was isolated in PTX-treated chimera-expressing CHO G alpha 16z49 cells, reversals of potency order were observed with respect to responses in untreated cells. These were most striking for 17 phenyl PGD2, 15 R 15 methyl PGF2 alpha, 15 deoxy delta 12,14 PGJ2 and 15 R 15methyl PGF2 alpha. Alterations of potency order were also observed in non-chimeric cells (G beta gamma i/o coupling) compared with PTX treated chimera-expressing cells. These were most striking for indomethacin, 16,16 dimethyl PGD2, delta 12 PGJ2 and 9,10 dihydro 15 deoxy delta 12,14 PGJ2. In [35S]-GTP gamma S accumulation assays using membranes prepared from non-chimeric cells and presumably reporting G alpha i/o coupling, agonist pharmacology was similar to G alpha 16z49 mediated calcium mobilisation data. However, the data were markedly different from G beta gamma i/o-mediated calcium mobilisation data generated in non-chimeric cells. These differences were most apparent for 13,14 dihydro 15 keto PGD2, 15 deoxy delta 12,14 PGJ2 and indomethacin. Desensitisation of agonist-stimulated calcium mobilisation was also studied. PGD2 produced rapid & long-lasting desensitisation of hCRTH2 receptors in a biphasic manner suggesting that two desensitisation mechanisms may operate. At low concentrations of PGD2 desensitisation was PTX-insensitive suggesting that a non-Gi/o-protein mediated mechanism may be responsible. Other CRTH2 receptor agonists inhibited responses to subsequent PGD2 EC80 exposure in calcium mobilisation assays. Interestingly, a group of molecules devoid of agonism in the calcium assay also inhibited PGD2 responses. This group of molecules included 19 hydroxy prostaglandins A2, E2 & F2 alpha , and PGE2 and appeared to mediate their effects through a mechanism that did not involve a competitive interaction with PGD2. The data generated here show that CRTH2 receptor agonist pharmacology is critically dependent on G-protein coupling partner and assay methodology, and are strongly indicative of agonist-directed stimulus trafficking. The data are consistent with the notion that G beta gamma subunit activation is not a passive "on-off" event but is rather an active event triggered by agonist- and GTP-dependent conformation changes in both receptor and G alpha subunit molecules.